2002
DOI: 10.1034/j.1600-6143.2002.020211.x
|View full text |Cite
|
Sign up to set email alerts
|

The General Public's Concerns about Clinical Risk in Live Kidney Donation

Abstract: Difficulty in attracting live kidney donors may be related to fears regarding both the surgical procedure for kidney harvesting and future failure of the remaining kidney. We conducted a cross-sectional study of households in Maryland to identify public disincentives to living related kidney donation. In multivariate analyses, we assessed the independent effects of several factors on willingness to donate a kidney to a sibling. We also assessed thresholds for factors above which persons would not donate a kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 38 publications
6
50
0
3
Order By: Relevance
“…In potential living donors, FMD is the second commonest anatomical abnormality apart from multiple renal arteries and is observed in 2.0-6.6% of the potential donors by angiography (2,6,12). FMD is diagnosed most often in young and middle-aged women, who currently constitute a large part of potential live donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In potential living donors, FMD is the second commonest anatomical abnormality apart from multiple renal arteries and is observed in 2.0-6.6% of the potential donors by angiography (2,6,12). FMD is diagnosed most often in young and middle-aged women, who currently constitute a large part of potential live donors.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the disadvantages of live donation includes a perioperative mortality of 0.03%, morbidity of 0.2%, minor complications of <10% and the unknown risk of renal failure from solitary kidney in the long term. Even though the long-term follow-up did not show significant increase in risk for renal failure (2)(3)(4), this degree of safety can only be achieved by very cautious donor selection. It is likely that rapid increase in live kidney donation may lead to relaxation in acceptance criteria, and introduction of less invasive and more cost-effective means of evaluation of the potential donors.…”
Section: Introductionmentioning
confidence: 99%
“…4,11 Our findings of significant improvements in transplant outcomes for black recipients may help to alleviate unmet concerns that might impede black patients' willingness to pursue transplantation. 13,[17][18][19] Standardized transplant education, which incorporates the latest research findings, might also help to improve transplant knowledge and communication among black patients, their families, and health-care providers not directly involved in the transplant process (e.g., primary care providers and general nephrologists). 15,19,28 Our study was limited by the variables captured in SRTR, including provider-reported race, which has the potential for misclassification bias.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal KT education and provider communication might engender unmet concerns about KTand facilitate less willingness to pursue KT among black patients. 14,[17][18][19] In general, patient and graft survival after KT have dramatically improved in the United States, 4 reflecting advances in transplant care in recent years. We hypothesized that advances in immunosuppression and post-transplant management might differentially benefit black KT recipients (who were disproportionately burdened by immunologic barriers) and contribute to reduced racial disparities in KT outcomes.…”
mentioning
confidence: 99%
“…The general public's concerns of living kidney donation is the length of a hospital stay, out-of-pocket expenses, size and appearance of a scar, and the donor risk of developing kidney failure (Boulware LE, et al 2002 ). In this respect, it is quite important process to inform prospective donor of these issues.…”
Section: Ethical Issue In Living Kidney Donationmentioning
confidence: 99%